How Managerial Overconfidence Shapes M&A Decisions: A Systematic Literature Review - Khamada Novel; Lalu Hamdani Husnan; Siti Aisyah Hidayati (LP2M IAIN Palopo, 2026)
This study presents a systematic literature review of 34 empirical articles published between 2004 and 2025 to examine how managerial overconfidence shapes merger and acquisition (M&A) decisions and outcomes. Using PRISMA 2020 guidelines, the review synthesizes evidence across global contexts, covering both developed and emerging markets. The findings show that overconfident CEOs and managers tend to initiate larger, riskier, and more frequent acquisitions, often resulting in weaker post-merger performance and unfavorable market reactions. The effects of overconfidence are further amplified by investor sentiment, decision framing, and organizational dynamics. Corporate governance (particularly board independence and internal control systems) emerges as a key moderating factor that can constrain biased decision-making. Recent studies also introduce improved measurement approaches, including synergy forecast error and machine-learning models. The review highlights the need for more research in emerging markets such as Indonesia, where context-specific proxies and governance structures may influence the behavioral dynamics of M&A.